MENINGKATKAN SIKAP MORAL ANAK MELALUI PERMAINAN ULAR TANGGA ANAK USIA 5 TAHUN DI TK ALJAUHAR - Nafisa, Sitti; Fikri, Mu’tasim; Vitasari, Any Diana (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2025)
Morality is a belief about right and wrong, good and bad, in accordance with social consensus, which underlies actions or thoughts. Deviant moral behavior was observed in class B. The results of preliminary observations and interviews indicated that several students in class B displayed impolite behavior toward their classmates, used inappropriate language, and so on. The observations further revealed that, in addition to the low quality of children’s moral development, another factor hindering moral learning was the teacher’s use of less varied methods, which made the children feel bored. The aim of this study is to improve children’s morality through the application of a Snakes and Ladders game as a learning medium. The subjects of this study were 15 children from class B. This research is a classroom action research (CAR). The instrument used was the daily lesson plan (RPPH). In the assessment aspect of children’s morality, the results in cycle I showed that the average percentage obtained by the children across four aspects was 21.675% (Developing as Expected/MB). In cycle II, the average percentage of children’s morality increased to 81.675%, which can be categorized as Very Well Developed (BSB).